Use of Intraoperative Frozen Section in the Surgical Management of Patients with Nonmelanoma Skin Cancer - LiAnn Loh; Priya Tiwari; Jingtzer Lee; O-Wern Low; Vigneswaran Nallathamby; Hanjing Lee; Jane Lim; Thiam Chye Lim; Yan Lin Yap (Journal of Skin Cancer)
Background. Intraoperative frozen section (IFS) is often utilised in the surgical treatment of nonmelanocytic skin cancer (NMSC) in sensitive facial regions when Mohs micrographic surgery (MMS) is not available. Objective. To compare the outcome of NMSC patients with excision performed with and without IFS. Materials and Methods. A retrospective, single-centre study was performed on all patients who had undergone resection of NMSC with and without IFS control at the National University Hospital (NUH) from 2010 to 2015. Results. 116 patients were recruited, of which 86 had IFS and 30 did not. The complete excision rate of patients with IFS was higher at 87.2% (p=0.0194), need for secondary operation was lower at 1.2% (p=0.005), and need for postsurgery radiotherapy or chemotherapy was lower at 1.2% (p=0.001). The average duration of surgery in patients who underwent IFS was 95.4 minutes compared to 70.1 minutes in cases which did not undergo IFS. Conclusion. Our study showed an increased complete excision rate and reduced need for secondary surgeries and adjuvant therapy in patients with IFS. However, a longer operative duration was required. Use of IFS may be useful in patients with NMSC lesions in sensitive regions requiring complex reconstruction after tumour excision.